THE EFFECT OF THE THINK PAIR SHARE MODEL ON INTEGRATED THEMATIC LEARNING OUTCOMES IN SD - Tiara Annisa; Reinita Reinita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2022)
This study aims to determine the effect of the Think Pair Share (TPS) cooperative learning model on student learning outcomes in integrated thematic learning in class IV SD Cluster IV, Agam Regency. This type of research is quantitative research with experimental methods and Quasi Experimental design, in the form of Nonequivalent pretest-posttest control group design. The sampling technique used was cluster random sampling with a population consisting of several elementary schools in one cluster IV, Agam Regency, which was selected as the experimental class, namely class IV at SDN 13 Sungai Sariak and class IV at SDN 22 Koto Gadang as the control class. Based on the results of hypothesis testing using t-test, the results obtained tcount = 3.28 and ttable = 1.68 with a significant level of 0.05. Thus, tcount 3.28 > ttable 1.68, it can be concluded that Ha is accepted, that is, there is a significant influence from the application of the Think Pair Share (TPS) cooperative model on student learning outcomes in integrated thematic learning in class IV SD Cluster IV District. religion.